Payment Application Design Using Cart (Classification And Regression Tree) Method - Elfinda Lusiana Ika Pradita; Kurnia Paranita Kartika; Filda Febrinita (Universitas Muhammadiyah Sidoarjo, 2021)
This payroll application is used to calculate the amount of salary that will be received by the Lion Parcel Blitar courier. This study aims to help find solutions for admins to complete payroll tasks quickly and accurately by developing a payroll system that is easy to implement. This research uses the RND (Research and Development) method according to Sugiyono (2012), because this method is used to generate and test the effectiveness of a product. To facilitate the grouping of couriers delivering the most packages and delivering the least packages, the method used by the author in this study is the CART method with the final result being a confusion matrix class a ( <= 600 ) of 5 data and a confusion matrix of class b (> 600 ) of 3 data. In addition, Black Box testing is also used with a percentage of 92.3% and questionnaires to validators of 86.1%, as well as prospective users as testing applications with a percentage of 90.4%. So this application is declared very feasible.